2019
DOI: 10.1037/ccp0000389
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of an online machine learning-driven risk assessment and intervention platform for increasing the use of crisis services.

Abstract: Objective: Mental illness is a leading cause of disease burden; however, many barriers prevent people from seeking mental health services. Technological innovations may improve our ability to reach underserved populations by overcoming many existing barriers. We evaluated a brief, automated risk assessment and intervention platform designed to increase the use of crisis resources provided to those online and in crisis. Method: Participants, users of the digital mental health app Koko, were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 22 publications
2
44
0
Order By: Relevance
“…The app specifically targets suicidal behavior and proposes an interactive and proactive content that is an effective prevention strategy [8,[88][89][90]. Despite this scientific evidence, a recent literature review [60] identified very few suicide-specific apps (24) with safety planning (14) and that directly allow the user to seek support (13). Moreover, potentially harmful content that encourages self-harm and suicide [26] was identified, and many of the existing apps for suicide prevention have not been scientifically validated [48,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The app specifically targets suicidal behavior and proposes an interactive and proactive content that is an effective prevention strategy [8,[88][89][90]. Despite this scientific evidence, a recent literature review [60] identified very few suicide-specific apps (24) with safety planning (14) and that directly allow the user to seek support (13). Moreover, potentially harmful content that encourages self-harm and suicide [26] was identified, and many of the existing apps for suicide prevention have not been scientifically validated [48,60].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, apps are affordable and ubiquitous, and can be used in any situation, particularly during a crisis [46]. The WHO recommends them for people at risk of suicide [1] because they offer new opportunities to overcome some of the help-seeking barriers [14,[47][48][49], and enhance safety planning [43] in response to dynamic suicidal processes in real-time [24].…”
Section: Ecological Momentary Intervention For Suicide Preventionmentioning
confidence: 99%
“…More research is needed to identify where suicidal individuals go to cope, whether these sites or mobile apps are efficacious or iatrogenic, develop strategies to improve the detection of suicidal individuals online, and to develop and evaluate ways to deploy rapid interventions for individuals at risk for suicide. Indeed, intervention research into nimble deployment of intervention on online platforms shows promise to encourage individuals to use crisis services (Jaroszewski, Morris, & Nock, 2019). Furthermore, both intervention and public health research is needed to increase help-seeking behavior in men, potentially targeting factors such as stigma and embarrassment as ways to increase treatment utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning ML-based DDSSs, just like their impact on patient safety or physicians' performances, their acceptability in practice remains understudied (Peiffer-Smadja et al, 2019). Jaroszewski et al (2019) reported that, during clinical trials of their MLbased DDSS for mental illness prevention, only 28% of participants answered "very likely" to the question presented by the DDSS: "Be honest, how likely are you to try the resources I just shared?". Nadarzynski et al (2020) studied the acceptability of information systems dedicated to sexual health prevention.…”
Section: A Questionable Acceptabilitymentioning
confidence: 99%